Synthesis and characterization of a family of thioether-dithiolate-bridged heteronuclear iron complexes. Issue 21 (18th May 2017) - Zhang, Yahui; Yang, Dawei; Li, Ying; Wang, Baomin; Zhao, Xiangyu; Qu, Jingping
Abstract : Five heterotrinuclear complexes and one heterobinuclear complex are successfully synthesized. These complexes are all well characterized by various spectroscopy studies. Abstract : The thioether-dithiolate-bridged heterotrinuclear complexes [Cp*Fe(μ-1k 3 SSS ′:2k 2 SS -tpdt)M(μ-2k 2 SS :3k 3 SSS ′-tpdt)FeCp*][PF6 ]2 (Cp* = η 5 -C5 Me5 ; tpdt = S(CH2 CH2 S)2 ;2, M = Co;3, M = Ni;4, M = Pd) have been prepared by a reaction of [Cp*Fe(η 3 -tpdt)] (1 ) with complexes CoCl2, NiCl2 (PPh3 )2, and PdCl2 (PPh3 )2, respectively. Similarly, treatment of complex1 with CuCl(PPh3 ) or AgPF6 afforded two heterotrinuclear complexes, [Cp*Fe(μ-1k 3 SSS ′:2k 2 SS -tpdt)M(μ-2k 2 SS :3k 3 SSS ′-tpdt)FeCp*][PF6 ] (5, M = Cu;6, M = Ag), while reaction of1 with the complex AuCl(PPh3 ) gave a heterobinuclear complex, [Cp*Fe(μ-1k 3 SSS ′:2k 1 S -tpdt)Au(PPh3 )][PF6 ] (7 ). These complexes have been spectroscopically and crystallographically characterized. An X-ray diffraction analysis showed that complexes2, 3, 5, and6 feature a heterometal center binding four sulfur atoms of two tpdt ligands with a cis orientation. However, in the Pd-containing complex4, two tpdt ligands are arranged in a trans configuration. The μ eff data and EPR results indicate that complexes2, 4, 5, 6, and7 are paramagnetic and only complex3 is diamagnetic. Electrochemical experiments on these heteronuclear clusters were performed at room temperature. Discrepancy of the redox couples in the CV plots of these complexes indicates different one-electron transfer processes.